SHOPPING LIFESTYLE AS MEDIATING BETWEEN HEDONIC SHOPPING ON IMPULSE BUYING ONLINE AT MARKETPLACE - Viajeng Purnama Putri (Universitas muhammadiyah malang, 2020)
This study is to test the effect of hedonic shopping, shopping lifestyle to impulse buying online. This research sample of 100 respondents, taken based on Purposive Sampling .The data analysis uses PLSsoftware3. This path analysis technique will be used in testing the amount of contribution shown by the path coefficient on each path diagram of the causal relationship between variables Hedonic shopping (HS), Shopping Lifestyle (SL), on Impulse Buying (IB). Hedonic shopping support have a positive and significant effect on impulse buying. Shopping lifestyle positif effect on impulse buying and shopping lifestyle able to mediate the effect between hedonic shopping on impulse buying. Hedonic shopping and shopping lifestyle had positively and significantly influenced the consumer’ responses to impulse buying.The findings of this study contribute to the theory of impulse buying online, namely hedonic shopping and shopping lifestyle important factors in realizing impulse buying online.